EFEKTIVITAS MODEL PEMBELAJARAN GROUP INVESTIGATION DALAM MENINGKATKAN HASIL BELAJAR DI SMPS KATOLIK BERDIKARI RAJA - Eugrasia Bulazy Doko; Stefania Baptis Seto; Hilaria Melania Mbagho (Program Studi Pendidikan Matematika, 2023)
The formulation of the problem in this study is whether the group investigation type learning model is effective on mathematics learning outcomes in class VII students of the Independent Catholic Junior High School. This study aims to determine whether applying the group investigation learning model can improve mathematics learning outcomes for seventh graders at the Independent Catholic Junior High School. The research instrument used is a test of learning outcomes. The type of research used is quantitative research. From the result of this study, it can be seen that the group investigation learning model can affect the mathematics learning outcomes of class VII students of the Independent Catholic Junior High School. Indicators of the assessment of learning outcomes can be seen from the increased post-test scores of students. Based on decision-making through a comparison of the value of arithmetic with the t table it is known that 11.640 > 2.042 and it can be concluded that is rejected and is accepted, meaning that there are significant differences in mathematics learning outcomes for students by applying the group type cooperative learning model group investigation. In other words, the group investigation cooperative learning model is effective in improving learning outcomes.